New record of Lobophora rosacea (Dictyotales, Phaeophyceae) from Bach Long Vi Isd. Hai Phong province, Vietnam - Dam Duc Tien; Quynh Nga, Nguyen; Mai Anh, Nguyen Thi; Bich Ngoc, Nguyen Thi (Academia Journal of Biology, 2025)
Lobophora rosacea is newly reported from Bach Long Vi Island, Hai Phong province, Vietnam. Our specimens are very similar to L. rosacea recently described from New Caledonia and Hainan Island, China, not only in morphology but also in rbcL gene sequences. The plant grows clustered and attached to the substrate by a basal holdfast. Thallus has fan-shaped to circular, up to 10 cm wide and 7 cm tall, 117–123 µm thick, lax, predominantly erect, light orange. Thalli are attached to the substratum by basal rhizoids on the ventral surface. Thallus margin entire and composed of single cell layered medulla, 14.88 µm (11.28 - 19.16 µm) wide, 35.34 µm (31.49 - 38.74 µm) high, 82.39 µm (75.76 - 88.72 µm) long; three cell layered cortex on the dorsal, 9.85 µm (5.96 - 14.92 µm) wide, 8.03 µm (5.99 - 10.00 µm) high and ventral side respectively, 12.20 µm (8.79 - 15.14 µm) wide, 9.52 µm (8.10 - 12.14 µm) high. Reproductive structures are undetected.